1996
DOI: 10.1063/1.472111
|View full text |Cite
|
Sign up to set email alerts
|

The condensed phases of carboranes

Abstract: An atom–atom Lennard-Jones (LJ) model for the intermolecular potential of carborane molecules (B10C2H12) is developed and used in a series of classical constant-pressure molecular dynamics simulations of p-, m- and o-carborane crystals, at several temperatures and zero pressure. The potential model reproduces many structural and dynamical properties of these crystals, in particular the high temperature orientationally disordered plastic phase common to the three compounds. This work stresses the need of furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…These ligands are anticipated to be much more structurally rigid due to their cage-like nature than the Cu 4 S 4 cores. Importantly, the distance between M9 groups is substantially larger than the molecular distance in m-carborane crystal 17 , indicating that the M9 groups are not in van der Waals (vdW) contact, thus allowing them to move without mutual steric hindrance under compression.…”
Section: Main Textmentioning
confidence: 99%
“…These ligands are anticipated to be much more structurally rigid due to their cage-like nature than the Cu 4 S 4 cores. Importantly, the distance between M9 groups is substantially larger than the molecular distance in m-carborane crystal 17 , indicating that the M9 groups are not in van der Waals (vdW) contact, thus allowing them to move without mutual steric hindrance under compression.…”
Section: Main Textmentioning
confidence: 99%
“…Our simulations suggest that the reorientational relaxation of the fullerenes is nearly one order of magnitude slower than that of a low molecular-weight nonpolar aromatic molecular crystal such as benzene 36 ͑moment of inertia, I ϳ 14ϫ 10 −46 kg m 2 ͒ in this temperature range ͑ J = 0.5-6.0 ps͒, but somewhat more similar to that of car- boranes ͑I ϳ 5 ϫ 10 −45 kg m 2 ͒, despite the differences between the molecular rotational motions in these crystals. 37,38 It is also interesting to compare the behavior of C 60 in the C 60 -cubane crystal to the dynamics of the crystalline C 60 . Johnson et al 39 have investigated the rotational dynamics of C 60 in the solid state using NMR over the temperature range of 240 up to 331 K. They observed that the reorientational correlation time follows an Arrhenius temperature dependence with activation energy of approximately 1.4 kcal/mol for the rotor phase of crystalline C 60 .…”
Section: A Rotor-stator Phasementioning
confidence: 99%
“…All simulations were performed on a RHCC-NT- o -carborane (C 2 B 10 H 12 ) complex in which all four cavities were simultaneously occupied by a single carborane molecule. The complex was formed by inserting a modeled structure of an o -carborane molecule into each cavity of the measured structure of an RHCC-NT tetramer (PDB code 1FE6) 13 which was crystallized at T = 298 K. The Amber 99 force field parameters for o -carborane were obtained from literature 23 25 . Each RHCC-NT complex was solvated in water and Na + ions to neutralize the system.…”
Section: Methodsmentioning
confidence: 99%